Histopathological growth patterns in patients with advanced nodular lymphocyte‐predominant Hodgkin lymphoma treated within the randomized HD18 study: a report from the German Hodgkin Study Group. (15th August 2021) - Eichenauer, Dennis A.; Bühnen, Ina; Kreissl, Stefanie; Goergen, Helen; Fuchs, Michael; von Tresckow, Bastian; Rosenwald, Andreas; Klapper, Wolfram; Hansmann, Martin‐Leo; Möller, Peter; Bernd, Heinz‐Wolfram; Feller, Alfred C.; et al.
Summary: We retrospectively investigated histopathological growth patterns in individuals with advanced nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) treated within the randomized HD18 study. In all, 35/60 patients (58%) presented with atypical growth patterns. Patients with atypical growth patterns more often had stage IV disease ( P  = 0·0354) and splenic involvement ( P  = 0·0048) than patients with typical growth patterns; a positive positron emission tomography after two cycles of chemotherapy (PET‐2) tended to be more common ( P  = 0·1078). Five‐year progression‐free survival [hazard ratio (HR) = 0·86; 95% confidence interval (CI) = 0·49–1·47] and overall survival (HR = 0·85; 95% CI = 0·49–1·51) did not differ between the groups after study treatment with PET‐2‐guided escalated BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisone). Thus, advanced NLPHL is often associated with atypical growth patterns but their prognostic impact is compensated by PET‐2‐guided escalated BEACOPP.